The familiar enemy Chaucer, language, and nation in the Hundred Years War - Butterfield, Ardis (Oxford : Oxford University Press, 2009)
'The Familiar Enemy' examines the linguistic, literary, and cultural identities of England and France during the Hundred Years War. It explores works by Deschamps, Charles d'Orleans and Gower, as well as Chaucer who, the book argues, must be resituated within the context of the multilingual cultural geography of medieval Europe.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Chaucer, Geoffrey, -- d. 1400.; English literature -- Middle English, 1100-1500 -- History and criticism; French literature -- To 1500 -- History and criticism; English literature -- Middle English, 1100-1500 -- French influences; French literature -- To 1500 -- English influences; Nationalism and literature -- Great Britain -- History -- To 1500.; Nationalism and literature -- France -- History -- To 1500.